THE IMPACT OF INFLATION, CERTIFICATE OF BANK INDONESIA, AND EXCHANGE RATE OF IDR/USD ON THE INDONESIA COMPOSITE STOCK PRICE INDEX - Ekadjaja, Margarita; Dianasari, Daisy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2017)
This research is done with the aim to know whether some macroeconomic variables, which are inflation rate, certificate of Bank Indonesia (SBI) rate, and exchange rate of IDR/USD have an impact on the movement of the composite stock price index (IHSG) at the Indonesia stock exchange (BEI) partially and simultaneously in the period of 2006–2014. The research population is inflation rate, SBI rate, and exchange rate of IDR/USD. Data analysis in this research is multiple regression by using time series monthly data of 2006–2014. Research results show that partially inflation rate gives positive significant impact on IHSG, SBI rate has negative significant impact on IHSG, and exchange rate of IDR/USD has positive significant impact on IHSG. Simultaneously it shows that inflation, SBI rate, and exchange rate of IDR/USD have an impact on IHSG at BEI to the period of year 2006 – 2014. Those variables affect IHSG by 58,74%, while other variables affect IHSG by 41,26%. That information can be used by investors to make decision on their investment.Keywords: Inflation, SBI, Exchange rate, IHSG, BEI.